Journal ANALISIS PENVEMARAN NAMA BAIK DAN PENYALAHGUNAAN KEBEBASAN BEREKSPRESI DI JEJARING SOSIAL - Mahardika, Agies Noor (Jurnal Aktual Justice, 2025)
Social networks have become an integral part of modern life, facilitating communication, interaction and expression of individuals globally. However, the use of social networks also carries risks in the form of spreading content that damages reputations and abuse of freedom of expression. Analysis of defamation and abuse of freedom of expression on social networks is an important topic in this context. This research uses a qualitative approach by collecting data from various social networking platforms, including case studies involving reputation-damaging content and abuse of freedom of expression. Analysis is carried out using a conceptual framework that identifies behavioral patterns, motivations and the impact of the abuse. The research results show that defamation on social networks can have a serious impact on individuals and organizations. Reputational damaging content can spread quickly and create a negative image that is difficult to erase. Meanwhile, abuse of freedom of expression is often driven by motivations such as political, economic or personal interests, resulting in intense and sometimes toxic debates. This analysis underscores the importance of managing and monitoring content on social networks. These platforms need to adopt stricter policies against abuse and reputation-damaging content, while still respecting freedom of expression. Additionally, individuals also need to increase their digital literacy to recognize and respond wisely to reputation-damaging content. Awareness of potential risks in social networks must increase, and joint efforts from users, platforms and governments are needed to create a safer and healthier online environment. In this way, we can harness the positive potential of social networks while maintaining the good name and integrity of individuals and society.